The Implementation of Islamic University Social Responsibility in Indonesia - Acynthia Ayu Wilasittha; Tantina Haryati; Sofie Yunida Putri; Nanda Wahyu Indah Kirana (Nusantara Science and Technology Proceedings, 2022)
This research aims to analyze the implementation of Islamic University Social Responsibility in Indonesia. This is a literature review study that was conducted by searching the keyword “Islamic university social responsibility” and filtered to specific literature that refers to the implementation of university social responsibility in Islamic Universities in Indonesia. The results show that not many University Social Responsibility studies are related to Islam because in measuring University Social Responsibility they still use green accounting indicators that consist of environmental awareness, environmental involvement, environmental reporting, and environmental audit. Numerous research has been found to suggest fresh approaches to adopting university social responsibility, like using the Maslahah or Maqashid Syariah concepts. These new models are anticipated to address issues with reporting environmental activities for which there are no guidelines and to offer direction in adopting USR, which is linked to Islamic religious values.